PENGARUH FAKTOR MODEL, MUTU DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SARUNG TENUN PADA USAHA KECIL DAN MENENGAH (UKM) DI PARENGAN MADURAN LAMONGAN - Ana Fitriyatul Bilgies; Hafidz Nasrullah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
The purpose of this study was to analyze the effect of model, quality and price factors on purchasing decisions on woven sarong products in Small and Medium Enterprises in Parengan Maduran Lamongan. The data used in this study are primary data obtained from the questionnaire. The population in this study is 1650 Consumers at CV. Paradila and 1350 CV. Bintang Mas, resulting in a total population of 3000 consumers. While samples with Slovin formula obtained as many as 97 people. Sampling Technique. In this research, purposive sampling method was used. Purposive sampling is a sampling technique with certain considerations. The analytical techniques used are validity, reliability, classical assumptions, multiple linear regression, T test and F test and R determination of research results. The results of the multiple linear regression equation formed are as follows: Y = 0.465+ 1.025 X1 + 0.219 X2 + 0.045 X3 + e. Based on the F test, it can be seen that the Fcount value is 128.51> Ftable value of 2.70. This proves that the Model, Quality and price variables simultaneously influence the Purchasing decision of woven sarongs. 1,661, Quality (X2) 3,164> 1,661 and Price (X3) 0,418 <1,661. Thus the Model variable that most influences the Decision variable Purchases woven sarongs while the coefficient of determination test is equal to 77.9% The decision to purchase woven sarongs is influenced by variations in the three variables used in the study, the remaining 22.1% are influenced by other variables